Ethnomusicology, Queerness, Masculinity Silence=Death - Amico, Stephen (Springer Nature, 2024)
This open access book explores the disciplinary, disciplined, and recent interdisciplinary sites and productions of ethnomusicology and queerness, arguing that both academic realms are founded upon a destructive masculinity-indissolubly linked to coloniality and epistemic hegemony-and marked by a monologic, ethnocentric silencing of embodied, same-sex desire. Ethnomusicology's fetishization of masculinizing fieldwork; queerness's functioning as Anglophone master category; and both domains' devaluation of sensuality and experience, concomitant with an adherence to provincial, Western conceptions of knowledge production, are revealed as precluding the possibilities for equitable, dialogic pluriversality. Enlisting the sonic as theoretical intervention, the disciplined/disciplining ethno and queer are reimagined in relation to negative emotions and intractable affect, ultimately vanquished, and replaced by explorations of sound, sex/uality, and experiential somaticity within a protean, postdisciplinary space of material/epistemic equity. This uncompromising, long-overdue critique will be of interest to researchers and students from numerous theoretical backgrounds, including music, sound, gender, queer, and postcolonial/decolonial studies.